Transformasi Paradigma Ushul Fiqih: Kontinuitas Dan Perubahan Dalam Pemikiran Hukum Islam - Muhammad Najib (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
Science is always developing and will continue to develop with the times, as is the science of ushul fiqh. This scientific discipline has periods or phases in its development. Starting from the embryonic phase until the modern century. This article aims to provide a comprehensive understanding of the development of the science of ushul fiqh and explore paradigm shifts in ulus fiqh thinking from the early period to the modern era. These include analyzing the factors that cause paradigm changes, continuity in the principles of fiqh, and the impact of this transformation on the understanding of Islamic law in the contemporary context. The methodology used is descriptive qualitative. The results of the analysis of the development of ushul fiqh show that change is important, because problems are always developing. Likewise, the science of ushul fiqh, from the embryonic phase to the modern phase, from mutaqaddimin to mutaakkhirin. The changes, problems and perspectives we face are of course different, so that all existing problems can be answered optimally. Even though the methods are different, in principle they have the same goal, namely how to ground the Islamic Salih Li Kulli Zaman Wa Makan law.